Vaccinology : an essential guide - Milligan, Gregg N.; Barrett, A. D. T. (Alan D. T.) (Chichester, West Sussex ; Hoboken, NJ : Wiley Blackwell, 2015)
Vaccinology: An Essential Guide outlines in a clear, practical format the entire vaccine development process, from conceptualization and basic immunological principles through to clinical testing and licensing of vaccines. With an outstanding introduction to the history and practice of vaccinology, it also guides the reader through the basic science relating to host immune responses to pathogens. Covering the safety, regulatory, ethical, and economic and geographical issues that drive vaccine development and trials, it also presents vaccine delivery strategies, novel vaccine platforms (including experimental vaccines and pathogens), antigen development and selection, vaccine modelling, and the development of vaccines against emerging pathogens and agents of bioterror. There are also sections devoted to veterinary vaccines and associated regulatory processes. Vaccinology: An Essential Guide is a perfect tool for designed for undergraduate and graduate microbiologists and immunologists, as well as residents, fellows and trainees of infectious disease and vaccinology. It is also suitable for all those involved in designing and conducting clinical vaccine trials, and is the ideal companion to the larger reference book Vaccinology: Principles and Practice.
The history of vaccine development and the diseases they prevent / Martin G. Myers -- Vaccine development pathway / David W.C. Beasley -- Control and eradication of human and animal diseases by vaccination / Nigel Bourne and Gregg N. Milligan -- Pathogenesis of infectious diseases and mechanisms of immunity / Jere W. McBride and David H. Walker -- The host immune response, protective immunity, and correlates of protection / Gregg N. Milligan -- Adjuvants : making vaccines immunogenic / Gregg N. Milligan -- Discovery and basic science phase of vaccine development / Gavin C. Bowick -- Microbial-based and material-based vaccine delivery systems / Alfredo G. Torres, Jai S. Rudra, and Gregg N. Milligan -- Licensed vaccines for humans / Alan D.T. Barrett -- Veterinary vaccines / A. Paige Adams -- Development of vaccines for microbial diseases / Dennis W. Trent and David W.C. Beasley -- Regulatory path to vaccine licensure / Dennis W. Trent -- Veterinary vaccines : regulations and impact on emerging infectious diseases / A. Paige Adams -- Vaccine manufacturing / Dirk E Teuwen and Alan D.T. Barrett -- Clinical evaluation of vaccines / Richard E. Rupp and Bridget E. Hawkins -- Vaccine recommendations & special populations / Richard E. Rupp and Bridget E. Hawkins -- Vaccine safety / Dirk E. Teuwen and Alan D.T. Barrett -- Understanding and measuring dynamics of infectious disease transmission / Christine M. Arcari -- Vaccines from a global perspective / Alan D.T. Barrett and Bridget E. Hawkins -- Political, ethical, social, and psychological aspects of vaccinology / Caroline M. Poland, Robert M. Jacobson, Douglas J. Opel, Edgar K. Marcuse, Gregory A. Poland.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Vaccines; Vaccination; MEDICAL -- Pharmacology; Vaccination; Vaccines; Medical; Vaccines -- pharmacology; Vaccines -- therapeutic use; Drug Discovery; Vaccination; Electronic books